2020
DOI: 10.5670/oceanog.2020.208
|View full text |Cite
|
Sign up to set email alerts
|

The Antarctic Ice Sheet: A Paleoclimate Modeling Perspective

Abstract: use, sharing, adaptation, distribution, and reproduction in any medium or format as long as users cite the materials appropriately, provide a link to the Creative Commons license, and indicate the changes that were made to the original content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 126 publications
(193 reference statements)
1
9
0
Order By: Relevance
“…However, sea level estimates generally fall into the range of 15-20 m at 3 Ma and 20-35 m at ca. 3.5-4.5 Ma (Miller et al, 2012(Miller et al, , 2019(Miller et al, , 2020Hearty et al, 2020), consistent with melting of the EAIS in the Wilkes and Aurora Basins suggested by models (DeConto and Pollard, 2002) and sediment tracer data (e.g., Bertram et al, 2018; see Gasson and Keisling, 2020). This warmer Early Pliocene world was more sensitive to precessional and eccentricity forcing than the cooler Late Miocene, though the 41 kyr tilt cycle still dominated sea level changes.…”
Section: History Of Gmsl Changessupporting
confidence: 76%
“…However, sea level estimates generally fall into the range of 15-20 m at 3 Ma and 20-35 m at ca. 3.5-4.5 Ma (Miller et al, 2012(Miller et al, , 2019(Miller et al, , 2020Hearty et al, 2020), consistent with melting of the EAIS in the Wilkes and Aurora Basins suggested by models (DeConto and Pollard, 2002) and sediment tracer data (e.g., Bertram et al, 2018; see Gasson and Keisling, 2020). This warmer Early Pliocene world was more sensitive to precessional and eccentricity forcing than the cooler Late Miocene, though the 41 kyr tilt cycle still dominated sea level changes.…”
Section: History Of Gmsl Changessupporting
confidence: 76%
“…Ice-sheet models can be tested against those past changes, but the uncertainties in past configurations remain large enough that they translate into major uncertainties in projections. 66,144,145 Improved understanding of past changes is thus required to ascertain, for example, whether marine ice-cliff instability has occurred in the past 146 and, if so, the conditions that led to it occurring. We note, though, that future forcing may move outside of the envelope of paleoclimatic forcing, perhaps bringing novel behaviors, and requiring physics-based models calibrated against laboratory data.…”
Section: Future Research Directions To Improve Sea-level Projectionsmentioning
confidence: 99%
“…Understanding ice‐volume (sea‐level) and deep‐sea temperature variations over the past 40 million years is important for many lines of research. For example, it will lead to (a) a better understanding of ice sheet (in‐)stability under different climate conditions, with implications for sea‐level responses to anthropogenic warming (e.g., Bamber et al., 2019; P. U. Clark et al., 2016; DeConto & Pollard, 2016; DeConto et al., 2021; Foster & Rohling, 2013; Gasson & Keisling, 2020; Gomez et al., 2020; Gornitz et al., 2019; Lear et al., 2021; Pollard et al., 2015; Rohling, Haigh, et al., 2013; Umgiesser et al., 2011). Sea level records, together with deep‐sea temperature records, are also essential for (b) improving insights into the processes involved in changing Earth's long‐term climate state (e.g., Boettner et al., 2021; DeConto & Pollard, 2003; De Vleeschouwer et al., 2017; Foster & Rohling, 2013; Katz et al., 2008; K. G. Miller et al., 2020; Rohling et al., 2021; Westerhold et al., 2020); and (c) assessing whether, and to what extent, Earth's climate sensitivity to radiative forcing changes depended on the initial climate state, with relevance for anthropogenic climate change (e.g., Hansen et al., 2007, 2008; Köhler et al., 2010; Masson‐Delmotte et al., 2010; PALAEOSENS, 2012; Rohling et al., 2012, 2018; Stap et al., 2018; von der Heydt et al., 2016).…”
Section: Introductionmentioning
confidence: 99%